Andere Ästhetik Grundlagen - Fragen - Perspektiven - Gerok-Reiter, Annette; Bauer, Matthias; Robert, Jörg; Pawlak, Anna (Andere Ästhetik - Koordinaten, 2022)
The CRC research project Different Aesthetics aims to change perspectives in aesthetic discussions by directing attention to the 2000-year history of European art and culture before the 18th century.